Influence of Repairing Using Welded Steel Patches on Structural Integrity of a High Pressure Gas Pipeline - Jan Kec; Ivo Cerny; Jan Lustinec; Romana Pavelkova (Communications - Scientific letters of the University of Zilina, 2017)
The present paper deals with complex material properties of DN 300 pipeline from the section Olesna – Barchov. The work was aimed at experimental verification of the effect of welded-on cover patches on the pipeline integrity. Two types of welded-on cover patches were evaluated. In the first case, just a single patch – steel plate was welded into the pipeline wall, replacing the damaged area. A lack of root fusion was found by means of the NDT. In the second case, the primary patch welded into the wall was covered by an auxiliary patch welded over the first one. No imperfection of the weld integrity was shown in the second case. The experimental programme contained an evaluation of the resistance of the repaired section to 10 000 pressure cycles induced by the inner water pressure at R = 0 cycle load asymmetry and maximum pressure of 6.3 MPa. The effect of these repairs on the limit state of the pipeline was verified by means of hydrostatic burst test. The tests comprised the evaluation of fracture surface morphology.